2018
DOI: 10.4236/cn.2018.104014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Information Literacy Skills on Postgraduate Students’ Use of Electronic Resources in Private University Libraries in South-West, Nigeria

Abstract: The introduction of new technologies has had a significant influence on teaching, learning and research activities in universities. This has offered university libraries opportunities to provide information resources in a variety of formats. This study investigated the influence of information literacy skills on postgraduate students' use of electronic resources in private university libraries in Nigeria. The study adopted the survey research design. The study population comprised 2805 postgraduate students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Adeniran (2018) investigated the influence of information literacy skills and computer self-efficacy on postgraduate students’ use of e-resources in private university libraries in Nigeria. Findings revealed that there was a significant positive correlation between information literacy skills and the use of e-resources ( r = 0.28, p < 0.05).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adeniran (2018) investigated the influence of information literacy skills and computer self-efficacy on postgraduate students’ use of e-resources in private university libraries in Nigeria. Findings revealed that there was a significant positive correlation between information literacy skills and the use of e-resources ( r = 0.28, p < 0.05).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berdasarkan ledakan sumber daya informasi dan layanan di perpustakaan akademik, beberapa penelitian menunjukkan bahwa sebagian besar mahasiswa tidak dapat menggunakan sumber daya informasi secara efektif dan efisien karena kurangnya atau tidak memadainya keterampilan literasi informasi mereka (Aderibigbe & Ajiboye 2011;Suleiman, 2012;Adeniran & Onuoha, 2018). Permasalahannya yang muncul dalam minimnya ketergunaan koleksi perpustakaan pada penelitian Suleiman ditunjukkan bahwa mahasiswa belum memiliki keterampilan literasi informasi yang diperlukan untuk menggunakan informasi, serta sifat perilaku pencarian informasi lainnya (Suleiman, 2012).…”
Section: Pendahuluanunclassified
“…This skill also requires an individual to identify the exact research problem, type of information to solve the identified problem, itemize the specific questions and hypothesize from the problem, which provides a clear focus of what is needed (Adeniran and Unuoha, 2018). Skill to identify the extent of information need involves the ability to understand and articulate the scope of information needed (Belay and Bramo,2017 ).…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Therefore, the ability to access information can be defined as the ability to search for information, find and obtain the information from a given source (Bolek et al , 2018). An individual does not only find resources, but also be able to access the desired information from sources of information through search tools and extract specific information from the sources (Adeniran and Unuoha, 2018).…”
Section: Theoretical Studiesmentioning
confidence: 99%